Comparison between glass reactor - modified gas stripping method (MGSM) and stainless steel reactor - MGSM in determining Henry’s law constant for fluorotelomer alcohols (FTOHS) - Huang, Hong Wei. (2010)
The increasing concentrations of Fluorotelomer alcohols (FTOHs) have lead to an increase in environmental concerns. In this study, we study the water-partitioning coefficients of FTOHs compounds to give a better understanding of their transboundary movement in the atmosphere since it describe the partitioning of these compounds between the key phases of air and water. Modified Gas-Stripping technique is used to determine the Henry’s Law constant (Kaw) for the main compounds in FTOHs since it is a high volatile compounds. In this analysis of FTOHs, 4 main compounds are studied - 4:2 FTOH, 6:2 FTOH, 8:2 FTOH and 10:2 FTOH. Two types of reactors – Glass column reactor and Stainless Steel reactor are used to compare their result. The main objective is to compare their consistency in water-partitioning coefficients result of the FTOHs compounds. Experiments are varied with different spiking concentrations, different sampling intervals as well as temperature difference. Analysis of Henry’s Law constant (Kaw) of FTOHs compounds are done to observe their general trend with different temperature and different chain length.